Make yourself at home: networked domestic space, place and narrative in middle class South African everyday life - Hiltermann, Jaqueline Elizabeth (Centre for Film and Media Studies, 2019)
Domestic space and place, as well as how we conceptualise the home, are shifting in response to changes in digital and SNS technologies, and our relationships with such technologies. The home is not only the building in which we live, but a networked assemblage of material and digitally mediated space and place. This study examines predominantly white middle class arrangements of domestic space and place in South Africa, which provides insight into a relatively unexplored aspect of digital culture: the performance of domesticity via SNS, particularly Facebook. Furthermore gendered and racialised power dynamics and privilege in everyday life were investigated through a digital ethnography and critical discourse analysis of posts by 50 Facebook users. This data was supplemented by interviews and in-situ observations of five couples drawn from the broader sample. In combination, these methods revealed how space, place, and domestic responsibilities are secured through narrative practice. Through this study I show how Facebook has emerged as a collaborative platform where storytelling practices are influenced by the site architecture and algorithm. Facebook has opened up the private space of the home allowing domestic space, place, and practice to steadily gain visibility. This visibility, analysed in conjunction with Actor-Network Theory, revealed that homes, and narratives about the homes, are networked and dependent on relationships between actants. The home, and the relationships that stabilise it, are also reflective of discourses and power relations. Human actors negotiated territory and network roles, and these negotiations reveal power and hierarchy. Women remain more tightly bound to the home because of cultural and historical gendered discourses, and as a result the white women participants in this study continue to create place and ascribe space in digitally mediated and material versions of their homes. Furthermore, the resurgence of middle class postfeminist accounts of domesticity have promoted domestic idealism and many women have migrated back to the home spurred on by popular media, and economic privilege that has allowed them to forego paid employment. This study also shows that white, middle class women participants were offered choices to construct their own postfeminist narratives of domesticity. On the other hand, the black women employed as domestic workers by these middle class couples, were largely absent from such narratives and conversations. Findings further suggest that domestic space and place remained the domain of white women participants, and that white men were able to renegotiate their domestic responsibilities because they remained distant from domestic narratives and conversations, where they were largely associated with domestic inadequacy.